The Impact of Bedside Interdisciplinary Rounds on Length of Stay and Complications. Issue 3 (1st March 2017) - Dunn, Andrew S.; Reyna, Maria; Radbill, Brian; Parides, Michael; Colgan, Claudia; Osio, Tobi; Benson, Ari; Brown, Nicole; Cambe, Joy; Zwerling, Margo; Egorova, Natalia; Kaplan, Harold
Abstract : BACKGROUND: Communication among team members within hospitals is typically fragmented. Bedside interdisciplinary rounds (IDR) have the potential to improve communication and outcomes through enhanced structure and patient engagement. OBJECTIVE: To decrease length of stay (LOS) and complications through the transformation of daily IDR to a bedside model. DESIGN: Controlled trial. SETTING: 2 geographic areas of a medical unit using a clinical microsystem structure. PATIENTS: 2005 hospitalizations over a 12‐month period. INTERVENTIONS: A bedside model (mobile interdisciplinary care rounds [MICRO]) was developed. MICRO featured a defined structure, scripting, patient engagement, and a patient safety checklist. MEASUREMENTS: The primary outcomes were clinical deterioration (composite of death, transfer to a higher level of care, or development of a hospital‐acquired complication) and length of stay (LOS). Patient safety culture and perceptions of bedside interdisciplinary rounding were assessed pre‐ and postimplementation. RESULTS: There was no difference in LOS (6.6 vs 7.0 days, P = 0.17, for the MICRO and control groups, respectively) or clinical deterioration (7.7% vs 9.3%, P = 0.46). LOS was reduced for patients transferred to the study unit (10.4 vs 14.0 days, P = 0.02, for the MICRO and control groups, respectively). Nurses and hospitalists gave significantly higher scores for patient safety climate and the efficiency of rounds after implementation of the MICRO model. LIMITATIONS: The trial was performed at a single hospital. CONCLUSIONS: Bedside IDR did not reduce overall LOS or clinical deterioration. Future studies should examine whether comprehensive transformation of medical units, including co‐leadership, geographic cohorting of teams, and bedside interdisciplinary rounding, improves clinical outcomes compared to units without these features.